The effect of extensive interval training, intensive intervals, and motivational training on the speed of athletes swimming 50 meters freestyle - Putri Ulandari; Hendri Neldi; Argantos Argantos (Jorpres (Jurnal Olahraga Prestasi), 2023)
Training programs in supporting an achievement are factors that need to be considered. The impact of these factors will result in the quality and quantity of skills possessed by athletes. This study aims to determine the effect of extensive interval training, intensive interval training, and motivation on the speed of swimming 50 meters freestyle of Agam Regency swimming athletes. This research method uses a quasi-experimental method that uses a treatment design by Level 2x2. The sample of this study was 16 Agam Regency swimming athletes. Swimming athletes' motivation data were measured using questionnaires to measure the speed of swimming 50 meters freestyle using the speed test of swimming speed 50 meters freestyle. Data analysis using two-path ANAVA at significance level α=0.05 and Shapiro-Wilk Sig. normality test 0.05 and continued with the Tukey test. The results of the data analysis showed that: (1) There is an overall difference in freestyle 50-meter swimming speed between the extensive interval training method and the intensive interval training method (Sig. 0.00 0.05) (2) There is an interaction between the interval training method and the motivation to train at the speed of the 50-meter freestyle swimming (Sig. 0.00 0.05) (3) In the highly trained training group, the extensive interval method is more effective than the intensive interval method (Sig. 0.003 0.05) (4) In the group that Having low training motivation, extensive exercise methods could not be different from the intensive interval method group (Sig. 0.057 0.05). So it can be concluded that there is a significant influence of extensive interval training, intensive intervals, and training motivation on the speed of athletes swimming 50 meters freestyle.